Răspuns :
y=1-3x inlocuind in prima
3x+3(1-3x)=-1
3x+3-9x=-1
-6x=-4
x=2/3
y=1-3x=1-3.2/3=1-2=-1
x=2/3
y=-1
3x+3(1-3x)=-1
3x+3-9x=-1
-6x=-4
x=2/3
y=1-3x=1-3.2/3=1-2=-1
x=2/3
y=-1
[tex]\left\{\begin{matrix}
3x + 3y = - 1 \: | \times ( - 1) \\
3x + y = 1\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
- 3x - 3y = 1\\
3x + y = 1\end{matrix}\right.[/tex]
[tex] - 3x + 3x - 3y + y = 1 + 1[/tex]
[tex] - 3y + y = 2[/tex]
[tex] - 2y = 2 \: | \div ( - 2)[/tex]
[tex]y = - 1[/tex]
[tex]3x + y = 1[/tex]
[tex]3x + ( - 1) = 1[/tex]
[tex]3x - 1 = 1[/tex]
[tex]3x = 1 + 1[/tex]
[tex]3x = 2[/tex]
[tex]x = \frac{2}{3} [/tex]
3x + 3y = - 1 \: | \times ( - 1) \\
3x + y = 1\end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix}
- 3x - 3y = 1\\
3x + y = 1\end{matrix}\right.[/tex]
[tex] - 3x + 3x - 3y + y = 1 + 1[/tex]
[tex] - 3y + y = 2[/tex]
[tex] - 2y = 2 \: | \div ( - 2)[/tex]
[tex]y = - 1[/tex]
[tex]3x + y = 1[/tex]
[tex]3x + ( - 1) = 1[/tex]
[tex]3x - 1 = 1[/tex]
[tex]3x = 1 + 1[/tex]
[tex]3x = 2[/tex]
[tex]x = \frac{2}{3} [/tex]